PREPOSITIONAL PHRASE AND ITS TRANSLATIONS FOUND IN THE NOVEL “BUDHA, A STORY OF ENLIGHTENMENT” - I Made Juliarta (EJI (English Journal of Indragiri) : Studies in Education, Literature, and Linguistics, 2021)
The novel "Budha, A Story of Englightenment" is one of the famous novels with New York Times Best Selling authors. This novel tells the story as an icon of peace and serenity. Some sentences with the prepositional phrase and its translation from English into Indonesian are found in this novel. Therefore, the author is interested in analyzing the translation process in translating the source text into the target text. The source text is analysed and viewed to find out the translation of the prepositional phrase. This study aims at analyzing the source text and gets the meaning and its translation. It is stated that a prepositional phrase is a group of words consisting of a preposition, its object, and any words modifying the object. A prepositional phrase also modifies a verb or a noun. This theory stated that there are two types of prepositional phrases. In simple preposition, preposition consists of a single prepositional particle. In complex preposition, the preposition can be formed by using two or three prepositional particles separated with a noun, an adjective, and an adverb. There are some complex prepositional phrases. Those areas for, except for, according to, by means, on the part of, etc. This present study is intended to: (i) identify the types of lexical and syntactical forms of the English prepositional phrases found in the data source "Budha, A Story of Englightenment," (ii) analyse the types of shifts of prepositional phrases that were applied in the translation from the source text into target text in the novel "Budha, A Story of Englightenment."